Aluminium anode activation research- a review (2012)
The aim of this paper is to review aluminum anode formulation and activating elements till date and discuss the possibility of further work based on recent trends in the use of nano or agro based materials. The performance of aluminum anodes is largely dependent on alloy composition and a good understanding of the relationships between the metallurgy and the anodic response of the alloys. Recent researches show that microalloying aluminum anodes with certain metallic composite oxides can significantly improve anode life and reduce costs. Suggestions for further work are also presented.